2005
DOI: 10.1111/j.1742-1241.2005.00373.x
|View full text |Cite
|
Sign up to set email alerts
|

Tension-free vaginal tape: avoiding failure

Abstract: A prospective, single-centre study to assess the outcome of incontinence surgery in the first 120 consecutive patients who had tension-free vaginal tape (TVT) by a single surgeon. All patients were initially seen at 3 months postsurgery, with a cough provocation test, measurement of residual urine volume and a satisfaction survey. At a mean of 26 months (6-42 months) after surgery, a validated telephone interview was performed. The operation was performed in accordance with the original technique described by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 12 publications
0
9
0
3
Order By: Relevance
“…There were also no cases of perineal pain which other studies have described [7] and attributed to possible close proximity of the tape to the obturator nerve. Urethral injury did not occur due to direct protection of the structure with the operator's finger during dissection.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…There were also no cases of perineal pain which other studies have described [7] and attributed to possible close proximity of the tape to the obturator nerve. Urethral injury did not occur due to direct protection of the structure with the operator's finger during dissection.…”
Section: Discussionmentioning
confidence: 74%
“…The functional results between TVT and TOT are the same in our practice and largely depend on patient selection [7] . DeTayrac et al [8] reported a 90% objective cure in the TOT group as compared with 84% in the TVT group, with relatively equal morbidity at 1 year (range 7-17 months) of follow-up.…”
Section: Discussionmentioning
confidence: 96%
“…En revanche, Singary [84], Koops [71] et Holmgren [85], dans des é tudes comparant les ré sultats du TVT 1 implanté pour traiter une incontinence urinaire d'effort pure ou une incontinence urinaire mixte, retrouvent une baisse significative des taux de succè s dans cette deuxiè me indication (72,4 versus 48 %, 81,3 versus 65,7 %, 85 versus 60 %).…”
Section: Incontinence Urinaire Mixteunclassified
“…Incontinence urinaire mixte (Tableau 5) Al-Singary et al [29], Koops et al [30] étudient l'influence pronostique de l'incontinence urinaire mixte préopératoire.…”
Section: Résultatsunclassified